Regulation of hemocytes in Drosophila requires dappled cytochrome b5. - Kleinhesselink, K.; Conway, C.; Sholer, D.; Huang, I.; Kimbrell, D.A. (Biochemical Genetics, 2011)
A major category of mutant hematopoietic phenotypes in Drosophila is melanotic tumors or nodules, which consist of abnormal and overproliferated blood cells, similar to granulomas. Our analyses of the melanotic mutant dappled have revealed a novel type of gene involved in blood cell regulation. The dappled gene is an essential gene that encodes cytochrome b5, a conserved hemoprotein that participates in electron transfer in multiple biochemical reactions and pathways. Viable mutations of dappled cause melanotic nodules and hemocyte misregulation during both hematopoietic waves of development. The sexes are similarly affected, but hemocyte number is different in females and males of both mutants and wild type. Additionally, initial tests show that curcumin enhances the dappled melanotic phenotype and establish screening of endogenous and xenobiotic compounds as a route for analysis of cytochrome b5 function. Overall, dappled provides a tractable genetic model for cytochrome b5, which has been difficult to study in higher organisms.